Iris Murdoch, Kesempurnaan, dan Moralitas - Fuad, Muhammad (Paradigma: Jurnal Kajian Budaya, 2011)
The paper brings Iris Murdochs article, The Idea of Perfection, of which three frames of ideas, Platoethics, inner experience, and moral concept were discussed. The goal of the idea of perfection isreaching Perfection by cultivating the inner experience which the social behaviorists challenged the notion of inner experience as the core role. It is not tangible, therefore it is meaningless. Besidesinner experience, Murdochs premise lies in morality, which is a magnetic but inexhaustible reality.Although no one can reach Perfection, it remains a measure of which human would direct theirlives and how far it will be for one can get close to it. Murdoch proposes love for it is capable forprogressive attempt to see a particular object clearly. The ways of love are understood in the moralcontext, therefore, the choice of which is arbitrary in a sense that they remain as effort to be just andimpartial. Moreover, in the political realm, the effort is challenged at its hardest, but again, the innerexperience, moral choice, and compassion are a possibility. The idea of perfection is practiced in orderthat the concept becomes a standard of operation in ones life. Thus, the cultivation of the ideal ofperfection is a continuing inner exercise.